Detection of genomic mutations in katG and rpoB genes among multidrug-resistant Mycobacterium tuberculosis isolates from Tehran, Iran - B. Motavaf; N. Keshavarz; F. Ghorbanian; S. Firuzabadi; F. Hosseini; S. Zaker Bostanabad (New Microbes and New Infections, 2021)
Multidrug-resistant (MDR) Mycobacterium tuberculosis strains, defined as resistant to at least isoniazid and rifampin, have emerged as a major worldwide health threat. Spontaneous point mutations in various genes of M. tuberculosis cause resistance to isoniazid, with the most frequent gene target being katG; and resistance to rifampin is usually due to mutation in the rpoB gene. The current study was aimed to detect the point mutations in the katG and rpoB regions related to isoniazid and rifampin resistance. A total of 203 respiratory specimens were collected from patients suspected of having tuberculosis respiratory infections referred to hospitals of Tehran, Iran, during 2018–2019. The isolation and identification of M. tuberculosis isolates were performed according to the WHO protocol. Drug susceptibility testing was carried out by proportional method. PCR analysis and sequencing were used to detect mutations in the selected katG and rpoB regions. Forty-four M. tuberculosis strains were isolated, of which 12 (27.3%) and 10 (22.7%) were resistant to isoniazid and rifampin, respectively. Ten isolates were resistant to both isoniazid and rifampin and were considered as MDR isolates. Of the ten MDR isolates, six (60%) carried mutations in both rpoB and katG. The most common mutations among isoniazid- and rifampin-resistant isolates were in codon 315 of the katG gene (70%) and codon 441 of the rpoB gene (50%), respectively. The results of this study indicated that MDR-TB continues to be a serious public health problem in Iran.